A társasági jogviszonyok szabályozása a német polgári jogi társaságban - Szikora, Veronika (Debreceni Jogi Műhely, 2004)
Partnership under the civil code is a harsh institution in Hungarian legal system. Despite of this fact, most of the European countries apply this legal entity a lot as a background for other, more complicated corporate forms. In my essay I demonstrate those rules in German Civil Code (BGB), which show the importance and opportunities of these partnerships. If we would like to describe the essentials of partnerships under the Civil Code, the most important question is the legal relations from both inner and external point of view. Internal relations mean an obligation between the parties, who form this partnership. It is natural that we can find both rights and commitments between founders. This is a contract but BGB says that all parties have equal rights and commitments in the same partnership. As a general rule of the Code, it is permissive, not cogent. BGB has basic regulation for operating such a partnership, but can be useful if founders live with this permissive opportunity and shape special rules for their partnership, which fit to their aims, functions, different financial potential of the parties. There is a chance for founders to neglect building a whole structure and organization for their partnership, if they want to operate it as an inner partnership, without external relations, focusing only for the rights and omissions between the parties. From all contract that establishes a partnership under the Civil Code membership rights follow. These rights cannot be transferred. A distinction can be made between administrational, common business management and financial rights. Rights to common business management can consist of right to information, right to supervision or the most important right to vote. Financial rights gather typical rights such as right to dividend or liquidity proportion. These rights are social omissions from the viewpoint of the partnership itself, as these are for the interest of the parties. The most important omissions of the founders are financial contribution to establish the partnership. This regulation results from that partnership is to promote common aim of the founders, and to achieve this, all of them have to make available pecuniary or non-pecuniary assets. According to a special rule of BGB, over against the other corporate forms, members of the partnership have no omission to increase or complete their assets. Management of the partnership is not only a right but an obligation too. A special omission is that all members and founders have to be loyal to the partnership. Because of the strong partnership character of this corporate form, this means that members have to keep the interest and aim of the partnership in view. They all are responsible for achieving the aim of the partnership and nobody can sit as a beneficiary. Loyal members have to keep secrets in connection with operating the partnership and of course the sudden obligation to inform the others of all events and experiences, which are in tight connection with the partnership and the interests of the parties. If any of the members breach these obligations, rules of damages can be applied in BGB. Assets of the partnership are special, because no separated corporate assets form. Financial and non-pecuniary contribution becomes the assets of the community of members. It is undividable and common. But these common assets are strictly separated from the private assets of the parties. Rights for profit and deficit are equal, but this permissive rule allows different regulation in the contract. The only cogent sentence is the prohibition of societas leoniana, i.e. nobody can be precluded of profit and deficit. External relations mean the representation of the partnership. In this case the most important law is the contract itself. In case of disagreement between the parties, there is a helping rule of BGB: members can act as a body. If we take into consideration the rules of liability, we can say that because of the lack of legal capacity of the partnership, individual liability has its important role. Generally this liability is unlimited, but there is a chance to agree with the creditor to limit liability. But this limitation is only valid for that legal transaction. Rules for partnerships under the Civil Code in Germany are more detailed and nuanced than in Hungary. Partnership is the basic type of civil law partnerships, such as limited partnership or general partnership. We have to consider that building up a more coherent regulation for these partnerships can be useful to categorize atypical corporations.